Purwarupa Pengendalian Media Kolam Terpal Untuk Sistem Budidaya Mina Padi - Arifin, Arifin; Riyanto, Agus; Hadikusuma, Mohd. Ilyas (Jurusan Teknik Elektro Politeknik Negeri Pontianak, 2024)
Mina rice cultivation is an integration of fish and rice cultivation in one location, which requires efficient time and energy management. Providing food and regulating water conditions are important aspects in this cultivation. Pond water temperature and pH have a significant effect on fish welfare, so monitoring both is very important. This research aims to design a prototype for controlling tarpaulin pond media for the mina padi cultivation system. The research method involves collecting data from various sources and studying the planned automated system of tools. Arduino Uno is the main component as a system regulator or controller, equipped with ultrasonic, temperature and pH sensors, as well as RTC to regulate the feeding schedule. Measurement data will be displayed via LCD to monitor pool conditions in real-time. Detailed design is carried out to ensure that the equipment meets the needs in cultivating mina rice.